2020
DOI: 10.3390/app10227988
|View full text |Cite
|
Sign up to set email alerts
|

Is Topical Application of Hyaluronic Acid in Oral Lichen Planus Effective? A Randomized Controlled Crossover Study

Abstract: Hyaluronic acid (HA) has anti-inflammatory and anti-edematous effects and, thus, could be promising in the treatment of oral lichen planus (OLP). The aim of the study was to evaluate the effects of topical hyaluronic acid, compared to placebo, on salivary levels of calprotectin, interleukin-6 (IL-6), and bacteria, as well as clinical and subjective parameters. Fourteen patients with confirmed OLP were included. After random selection, patients started with either 0.2% hyaluronic acid or a placebo gel for 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Five studies reported a high risk of bias [ 6 14 15 18 19 ] due to one or more risks owing to performance, detection, attrition, and reporting bias. Two other studies reported an unclear risk of bias in selection, performance, and detection [ 13 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported a high risk of bias [ 6 14 15 18 19 ] due to one or more risks owing to performance, detection, attrition, and reporting bias. Two other studies reported an unclear risk of bias in selection, performance, and detection [ 13 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 199 participants from 6 studies were included in the analysis of OLP lesion symptoms [ 6 13 15 18 19 20 ]. The pooled overall mean difference was 0.65 [95% CI: -1.80 to 3.09] which was not statistically significant (Z = 0.52, P = 0.60).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that topical use of corticosteroids can be absorbed and cause systemic side effects [10]. The most reported side effects of topical corticosteroids are the presence of acute candidiasis, burning sensation, mucosal atrophy, and dry mouth [11]. Another side effect that can occur is hypogeusia and systemic effects such as suppression of the hypothalamic-pituitary-adrenal axis and Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%